Plant uncoupling mitochondrial proteins - Eugenio Vercesi, Anibal; Borecky, Jiri; Godoy Maia, Ivan de; Arruda, Paulo; Midea Cuccovia, Iolanda; Chaimovich, Hernan (Annual Reviews, 2006)
Uncoupling proteins (UCPs) are membrane proteins that mediate purine nucleotide-sensitive free fatty acid-activated H(+) flux through the inner mitochondrial membrane. After the discovery of UCP in higher plants in 1995, it was acknowledged that these proteins are widely distributed in eukaryotic organisms. The widespread presence of UCPs in eukaryotes implies that these proteins may have functions other than thermogenesis. In this review, we describe the current knowledge of plant UCPs, including their discovery, biochemical properties, distribution, gene family, gene expression profiles, regulation of gene expression, and evolutionary aspects. Expression analyses and functional studies on the plant UCPs under normal and stressful conditions suggest that UCPs regulate energy metabolism in the cellular responses to stress through regulation of the electrochemical proton potential (Delta mu(H)+) and production of reactive oxygen species.
Keywords: uncoupling proteins; plant mitochondria; oxidative phosphorylation; reactive oxygen species; energy metabolism